Study of the Photodegradation of Nanocomposites Containing tio2 Nanoparticles Dispersed in Polyethylene and in Poly(Ethylene-Co-Octadecene) - Rabagliati-Canessa, F; Zapata-Ramirez, P (Elsevier Ltd, 2014)
Composites of polyethylene (PE) and poly(ethylene-co-1-octadecene) copolymer with 0.063 mol/L (LLDPE-1) and 0.38 mol/L (LLDPE-2) were synthesized by in situ polymerization using metallocene catalysts in the presence of titanium dioxide (TiO2) nanoparticles. There were two effects on the photoaged polymers: One was related to the insertion of comonomer in the polymer, which causes a large increase of chemiluminescence (CL) during photoaging, a behavior that is due to large branching of the polymer. The other effect was due to nanoparticles incorporated into the polymer, which promote and accelerate its photodegradation due to reactive species generated during irradiation. The photodegradation of the nanocomposites was confirmed by CL, carbonyl index (CI), degree of crystallinity (%?), and microhardness (MH), which increased with photoaging time. After photoaging, the viscosity molecular weight of the copolymers, and consequently of their respective nanocomposites, decreased markedly. LLDPE-2-5TiO2 nanocomposites had the highest degradation and presented an increase of the degree of crystallinity from 2 to 12% and also of the microhardness (ca. 90%) compared with the neat polymer. Furthermore, according to SEM analysis, after photoaging the polymers presented cavities of ca. 50 ?m. © 2014 Elsevier Ltd. All rights reserved.